Anticancer Activity Study of Modified Artocarpin Compound from Pudau Plant (Artocarpus kemando Miq.) - Tati Suhartati; Khalimatus Sa’diah; Yandri Yandri; Sutopo Hadi (Ital Publication, 2023)
This research is a continuation of the successful isolation of artocarpin from the root of Artocarpus kemando Miq reported in our previous study. In the previous study, the artocarpin was characterized with UV-Vis and FTIR techniques. In this follow-up investigation, the artocarpin was subjected to a transesterification reaction using acetic anhydride and pyridine as catalysts, and the product of the reaction was specified as compound 1. The compound 1 was further characterized with different techniques to gain more complete data and then tested for anticancer activity test against P-388 murine leukemia cells. Characterizations of the compound 1 using 1H-NMR and 13C-NMR techniques suggest that the modification reaction resulted in the conversion of the -OH groups at C2' and 4' at the artocarpin molecule to -OOCH3, and based on the MS analysis, the compound was proposed to have the molecular formula of C30H32O8. Another important feature of compound 1 that should be noted is the significant improvement in stability compared to the unmodified artocarpin. Anticancer activity tests against P-388 murine leukemia cells revealed that compound 1 has an IC50of 2.35 µg/mL, confirming that the compound is categorized as an active anticancer agent and suggesting that the compound has promising potential that deserves further investigations. Doi: 10.28991/ESJ-2023-07-03-05 Full Text: PDF